Flow-based market coupling: What drives welfare in Europe's electricity market design? - Simon Voswinkel; Björn Felten; Tim Felling; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2019)
Due to the call for further integration of European markets and the targeted climate goals, both European electricity systems and markets have undergone continuous changes over the last few decades. As part of these developments, the so-called Flow-Based Market Coupling (FBMC) superseded the previous net-transfer-capacity-based approach in Central Western Europe in 2015, aiming at a better representation of physics of the electricity grid as well as increased transparency of market results and procedures. Yet, the market coupling procedures have recently been exposed to criticisms questioning their transparency in aspects such as the determination of FBMC parameters, such as generation shift keys (GSKs) or selected critical branches. At the worst, doubts are even cast on realized welfare increases through FBMC. The paper at hand investigates the FBMC approach by analyzing the market outcomes as well as the corresponding redispatch requirements under different premises and FBMC varieties. Inter alia, results show that different GSK approaches have a significant effect when price zones are well-defined, i.e., when intra-zonal congestion is excluded. In the contrary case, GSK choices have less - or even statistically nonsignificant - impact. Furthermore, we show that FBMC is rather insensitive to forecast deviations of renewables infeed. However, changes to the remaining available margins and the selection of critical branches - as being proposed by regulators and the European Commission, respectively - can severely affect results in terms of redispatch quantities and overall welfare.
Keywords: Q40; Q41; Q43; Q49; C60; 330; Flow-based market coupling; Zonal pricing; Nodal pricing; Generation shift keys; Remaining available margin; Electricity grid modeling; Electricity market modeling; Electriciy market design; Congestion management; Welfare analysis